Payments for adding ecosystem carbon are mostly beneficial to biodiversity - Larjavaara, M.; Davenport, T.R.B.; Gangga, A.; Holm, S.; Kanninen, M.; Nguyen, D.T. (IOP Publishing, 2019)
Biodiversity conservation is often considered to be an important co-benefit of REDD+ and other mechanisms aiming to increase carbon in biomass and soil to mitigate climate change. This reasoning is based on the assumption that the level of biodiversity and ecosystem carbon are positively correlated. Firstly, however, studies have shown both positive and negative relationships. Secondly, incentives for additional ecosystem carbon do not trigger random or all potential changes in land-use, but often concentrate on one or a few specific changes that could have an opposite effect than the general trend indicates. Therefore, it is important to study biodiversity impacts of plausible measures to increase carbon. We obtained land-use scenarios on pathways to increase carbon based on 97 face-to-face interviews of local land-use experts in twelve landscapes in seven countries and five continents. We then conducted another set of face-to-face interviews with biodiversity experts yielding 2963 estimations concerning the value of land-use classes for 264 taxa of fauna and flora in these landscapes. We found positive carbon to biodiversity relationships in ten of the twelve landscapes. The biodiversity impacts of measures to increase carbon were positive in eleven of the twelve landscapes. Our results indicate that a random land-use change that increases biodiversity is also likely to increase carbon and vice versa.